Oral verrucous hyperplasia – A literature review - R. Santhosh Kumar; Divya Bose; Thayalan Dineshkumar; M. Harinisubasri; Rajkumar Krishnan; Rameshkumar Annasamy (Oral Oncology Reports)
Background: Oral verrucous hyperplasia (OVH) is considered an irreversible precancerous lesion that has the potential to develop into oral verrucous carcinoma. It might be challenging to diagnose these lesions both clinically and histopathologically. Hence the current review aimed to analyze the clinical and histopathological features of OVH and to determine their prognosis. Materials and methods: An electronic literature search was done in PubMed, and Google Scholar databases for identifying articles published between 2000 and 2023. Case reports or series or original articles published in the English language reporting information on oral verrucous hyperplasia were included in this review. Results: 15 articles were included of which 3 were case series, 10 were case reports, 1 was a retrospective study and 1 was a cohort study. Conclusion: OVH appears clinically as a verrucous plaque or mass. It shows a predilection for middle-aged and older adults, with male predominance. Patients with OVH should be treated similar to oral verrucous carcinoma and should be continuously monitored for disease recurrence and malignant transformation.